2014
DOI: 10.1186/1471-2296-15-48
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the barriers to identifying carers of people with advanced illness in primary care: triangulating three data sources

Abstract: BackgroundApproximately 10% of the UK population have an unpaid caring role for a family member or friend. Many of these carers make a significant contribution to supporting patients at the end of life. Carers can experience poor physical and psychosocial wellbeing, yet they remain largely unsupported by health and social care services. Despite initiatives for general practices to identify carers and their needs, many remain unidentified. Neither are carers self-identifying and requesting support. This study s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
133
0
7

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(144 citation statements)
references
References 36 publications
(45 reference statements)
4
133
0
7
Order By: Relevance
“…However, it may also be more difficult for people to identify themselves in a broad description, and with a more restricted definition, this recognition may be easier. In addition, research has shown that informal caregivers may prefer to think of themselves as relatives or friends of the person with care needs, not as an informal caregiver [21]. As a result, they may not always identify with the term 'informal caregiver' or 'carer' [21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it may also be more difficult for people to identify themselves in a broad description, and with a more restricted definition, this recognition may be easier. In addition, research has shown that informal caregivers may prefer to think of themselves as relatives or friends of the person with care needs, not as an informal caregiver [21]. As a result, they may not always identify with the term 'informal caregiver' or 'carer' [21].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, research has shown that informal caregivers may prefer to think of themselves as relatives or friends of the person with care needs, not as an informal caregiver [21]. As a result, they may not always identify with the term 'informal caregiver' or 'carer' [21]. This consideration is important for future caregiving studies, in which researchers should think carefully about the definition of informal care that they use [20], and researchers may want to consider avoiding the terms 'informal caregiver' or 'carer' when recruiting informal caregivers.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, as a research population, carers present a range of challenges that need to be addressed to facilitate their participation in research. Carduff et al (2014) proposes that carers may not identify themselves as carers, rather that they view the support they provide a being integral to their position as spouse, son/daughter. Additionally they may be reluctant to participate in research as they prioritise the needs of the person they are caring for and may feeling guilty about talking about their needs and feelings.…”
Section: Discussionmentioning
confidence: 99%
“…It became evident that the low response rate was associated with the distribution of the questionnaires by the HFNS rather than non-return of the questionnaires. commonly do not identify themselves as a carer but think of themselves as a relative or friend who is supporting a person with a debilitating condition (Barnes et al, 2005, Carduff et al, 2014.…”
Section: Discussionmentioning
confidence: 99%
“…17 This qualitative study was conducted with caregivers of individuals with advanced diseases and shows they require physical, practical, and psychosocial support to persevere through the demands of homecare. 18 This study shows that the the caregivers expressed many difficulties, which were linked to lack of support, human, material and financial resources, unpreparedness to deal with death in the context of terminality and social isolation. This study corroborates the findings of other studies addressing this topic.…”
mentioning
confidence: 86%